The Growing Role of Technology in Education: How Technology is Empowering Students and Teachers - Zainudin Zainudin (Penelitian dan Pengembangan Ilmu, 2024)
This research examines technology integration strategies in education through a systematic literature review which aims to identify effective approaches in increasing student engagement, learning motivation, and academic outcomes. Articles taken from internationally reputable databases such as Scopus Q1 were screened using strict inclusion and exclusion criteria and analyzed using the PRISMA method to ensure the validity of the findings. The research results show that strategies such as the flipped classroom, the use of Learning Management Systems (LMS), and the integration of mobile devices in learning are effective methods in achieving educational goals. Implications of this research include the need for continued investment in teacher training and the development of adequate technological infrastructure, as well as the adoption of appropriate pedagogical strategies. This study also acknowledges limitations, including potential bias in study selection and limited geographic and linguistic coverage. Future research is recommended to explore technology integration strategies in more diverse contexts and develop more effective teacher training models.